Improving academic writing through the use of a developmental Rubric: a case study - Md Zamin, Ainul Azmin (Penerbit UM Press, 2017)
Providing feedback for students in writing courses has been the subject of much scholarly discussion. While many researches have demonstrated that feedback can be an effective way to improve students’ writing skills, questions remain as to how the feedback should be delivered. Inspired by the works of Hyland and Hyland (2001), Goodrich (1997) and Ferris (2010), this qualitative study investigates the use of a developmental rubric in helping students on an English for Academic Writing (EAW) course as a way of providing feedback. A basic premise underlying this study is that writing is a process where students focus on improving their drafts rather than giving emphasis merely on their final product. This study utilized the developmental rubric via self-editing and peer feedback during the drafting stage. Through interviews the researcher gathered valuable insights from both the teachers and students. The findings showed that students were positive in using the rubric in terms of the detailed description of each item helping them to pinpoint their own errors, as well as learning from their friends. Teachers gave useful suggestions to improve the rubric further in terms of the presentations and items of language. Overall, the results show positive signs of acceptance among both students and teachers but there still remain areas for improvement.